Customer Decision Making Analysis in Choosing the eMarketplace which Provide Food Products - Fathan Nahar Azali; Moh. Wahyudin; Atris Suyantohadi (APTA and DTIP FTP UGM, 2020)
Entering the digital era, shopping activities no longer have to go directly to the seller to get the desired product, including food products such as fast food, beverages, and variou s cooking needs. Currently customers can meet all their needs just simply by accessing a n e-marketplace application developed by the company to order the desired product and t hen the product will be delivered to the courier to the home or where the customer is loca ted. Until 2018 there are at least 10 e-marketplaces in Indonesia that are growing rapidl y and have the most users, of which 6 of them provide food products. The process of deve loping e-marketplace applications has also become interesting to watch as an effort to op timize the marketing of agroindustry products in the digital age. This study wants to find out what attributes on the e-marketplace application platform that affect customers in the decision-making process to choose certain e-marketplace applications. To achieve these goals, the writer uses the Analytical Hierarchy Process (AHP) approach. And the results show that in the decision-making process customers consider 11 attributes contained in t he e-marketplace application platform. Some of them are product search attributes, selle r reputation information, payment methods offered, protection of customer data, and loca tion maps.